Driving Financial Success: Analyzing the Influence of Financial Management Expertise on Enhancing SME Performance - Kumar, Gaurav; Murty, Avn; Savitha, G. R.; Rao, Srinivasa; Padhy, Sangram; Miyan, Rahmuddin (International Review of Management and Marketing, 2025)
Small and Medium-Sized Enterprises (SMEs) play a crucial role in Uganda’s economic growth but often face early closures due to poor financial management. This study examined the impact of financial management competence on the financial performance of SMEs. Data were collected through self-administered and researcher-administered questionnaires and analyzed using SPSS version 28. The findings showed a weak but statistically significant positive correlation (r = 0.377, P < 0.01) between financial management competence and SME performance. Regression analysis revealed that financial management competence significantly contributed to improved SME performance (t = 5.083, P < 0.05). The study suggests that improving financial management skills can enhance business performance, reduce early closures, and encourages further research into other factors influencing SME success.